The potential of Rhizophora mucronata and Sonneratia caseolaris for phytoremediation of lead pollution in Muara Angke, North Jakarta, Indonesia - Maman Rumanta (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rumanta M. 2019. The potential of Rhizophora mucronata and Sonneratia caseolaris for phytoremediation of lead pollution in Muara Angke, North Jakarta, Indonesia. Biodiversitas 20: 2151-2158. Environmental pollution by heavy metals has become a serious problem in Jakarta Bay. Mobilization of heavy metals as a result of anthropogenic activities has caused the release of heavy metals into the environment, one of which is Pb. Several methods have already been used to clean up the environment from these kinds of contaminants, but most of them are costly and difficult to get optimum results. Recently, phytoremediation is an effective and affordable technological solution used to extract or remove inactive metals and metal pollutants from contaminated soil and water. This technology is environmentally friendly and potentially cost-effective. These study objectives are (i) to find the accumulating capability of Pb in each plant tissues (roots, stems, and leaves) of R. mucronata and S. caseolaris; (ii) to find stomatal morphological characters of R. mucronata and S. caseolaris. All samples (roots, stems, and leaves) were collected from Muara Angke mangrove forest in North Jakarta. The accumulation of Pb is higher in S. caseolaris leaves than in roots, and stems, and than those in R. mucronata. The concentrations of Pb in roots, stems, and leaves of S. caseolaris were respectively 4.83 ?g/g, 3.37 ?g/g and 15.57 ?g/g and in R. mucronata were 10.50 ?g/g, 5.13 ?g/g and 13.33 ?g/g. Generally, the stomata of mangrove species that live in polluted ecosystems are longer and wider than the stomata of the same mangrove species that live in a non-polluted ecosystem. This is strongly suspected of being related to the physiological adaptation of heavy metal accumulation. This study showed that S. caseolaris is the most suitable species as a phytoremediation agent in the Muara Angke mangrove ecosystem.